Geological and Geographical investigations in Kong Frederik IX’s Land.: Morphology, Sediments, Periglacial Processes and Salt Lakes. - Hansen, Kaj (Meddelelser om Grønland, 1970)
Sondre Stromfjord and its continu ation, the valley of Sandflugtdalen, constitute a morphological border between two types of landscapes. Towards the north the main morphological direction of valleys and ridges runs ENE-WSW parallel with the folding axes and diaclases of the Precambrian, whereas ice erosion seems to have influenced the relief much more towards the south where the main lines run SE-NW. The sediments found around Sandflugtdalen are surprisingly homogeneous silt deposits, regardless of their origin . The mean grain size is about 30 microns, the sorting is very good, and the content of both sand (> 62 ft) and clay ( < 4 μ) very low. There are several salt lakes in the area and a belt of water mosses (Drepanocladus aduncus) is often seen along their banks, at some places pressed together in ridges with a surface layer of 15-20 cm sphagnum peat with pure ice below Also hillocks, solifluction terraces and other periglacial forms are abundant in the area. The salt lakes of this area are peculiar in that their ion content differs strongly from that of other salt lakes. The salinity is about 3 °/00 , but sulphate ions are almost completely lacking. The reason is that in spite of the arid climate, evaporation is very low because of the low summer temperature (below 10°C) and in addition, the soil is kept moist by the slowly thawing permafrost. The area around the lakes is therefore covered with a rich and abundant vegetation. The 30-40 cm of the soil that will thaw during the summer months are consequently very rich in humus and have reducing conditions. Thus, sulphate ions contained in the water seeping through will be reduced to sulphide and precipitate in the soil together with the iron, whereas the chlorine ions, which do not produce insoluble compounds, will continue unchanged out into the lake.